Biopolymers Online 2002
DOI: 10.1002/3527600035.bpol3b10
|View full text |Cite
|
Sign up to set email alerts
|

Fermentative Production of Building Blocks for Chemical Synthesis of Polyesters

Abstract: Introduction Historical Outline Dicarboxylic Acids Succinic Acid Adipic Acid Diols 1,2‐Propanediol 1,3‐Propanediol 1,4‐Butanediol Hydroxy Acids Lactic A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 178 publications
0
4
0
1
Order By: Relevance
“…[5,6] In fact, the hazards associated with chemical manufacturing and increased concerns about process safety open up a new window for alternative biocatalytic synthesis. [7] To date, the microbial host system is considered the most appropriate means for biotechnological production of polymer building blocks for Nylons [8][9][10] or polyesters. [11,12] Furthermore, it has been reported that omega amino dodecanoic acid (ω-AmDDA) or 12 amino dodecanoic acid methyl ester (ADAME) are convenient monomers for Nylon 12 biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[5,6] In fact, the hazards associated with chemical manufacturing and increased concerns about process safety open up a new window for alternative biocatalytic synthesis. [7] To date, the microbial host system is considered the most appropriate means for biotechnological production of polymer building blocks for Nylons [8][9][10] or polyesters. [11,12] Furthermore, it has been reported that omega amino dodecanoic acid (ω-AmDDA) or 12 amino dodecanoic acid methyl ester (ADAME) are convenient monomers for Nylon 12 biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Marktwertschätzungen für aus Bernsteinsäure hergestellte Produkte belaufen sich auf über 400 Millionen US-Dollar pro Jahr [2]. Momentan wird der Jahresumsatz der Bernsteinsäure, größtenteils petrochemischen Ursprungs, auf circa 15 000 Tonnen geschätzt [3]. Bei einem kostengünstigeren Produkt, vornehmlich auf Basis nachwachsender Rohstoffe, könnte dieses Marktpotential zukünftig ansteigen.…”
Section: Problemstellungunclassified
“…Each of these are considered to have high "building block potential", either as monomers for the production of novel polyesters and polyamides [112] or as a starting material for a variety of commodity chemicals, currently produced petrochemically. Accordingly, these five carboxylic acids are to become economically viable products if low-cost fermentation routes can be developed and implemented on an industrial level.…”
Section: Carboxylic Acidsmentioning
confidence: 99%